SCHOOL INCLUSION: FROM WANTING TO DOING - Amilton da Costa, José (Revista Gênero e Interdisciplinaridade, 2025)
This article addresses school inclusion as a relevant and widely discussed topic in the educational landscape, analyzing the challenges and advances in Brazil, focusing on the transition from favorable discourse to effective practice. It begins with the understanding that inclusion goes beyond the enrollment of students with Special Educational Needs (SEN), requiring structural, formative, and cultural changes in the school environment. The objective is to discuss the tensions between the desire for inclusion and the implementation of truly inclusive pedagogical practices, proposing a reflection on teaching in diversity and the construction of a quality inclusive proposal, offering a critical and contextualized understanding of the topic. The study adopts a qualitative approach and a literature review, based on official documents and specialized authors, highlighting the role of educators in promoting accessibility and overcoming physical, communicational, and attitudinal barriers, in the name of social justice and human equity. Although progress has been notable, there is still a long way to go between the desire for inclusion and the implementation of inclusiveness, requiring political commitment, ongoing training, and the transformation of school practices.